Affecting determinants of trust in business relationships - Piricz, Noemi (Serbian Journal of Management, 2018)
Scholars claim that cooperation conflict and even competition can exist between the partners in business relationship. Why are there conflicts among business partners? The logical answer is permanent changes in the fields of politics, economics, regulations, social norms and technological systems. It can also happen that in a new business network a company has to cooperate with its former competitor. In a dynamic prospective, trust affects satisfaction. Satisfaction and conflicts are always perceived by business relationship partners. Different cultures evaluate a business relationship in different ways, therefore they have various views on how to start or develop business relationships. The aim of this paper is to investigate the complex effects of trust on perceived satisfaction, perceived conflict and among organizations in existing business relationships. In this research it was found that trust is affected by both satisfaction (positively) and conflict (negatively). Due to the lack of a widely accepted definition of trust in business and what determines it, this quantitative research may bring new thoughts to researchers or even support earlier models as well. In this empirical paper, quantitative research methods were applied and 315 valid questionnaires received from organizations registered in Hungary, independent of size and economic sector. The valid questionnaires were analysed by SPSS software using factor analysis and regressions.